(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
Departing from the (re)definitions of the notion of musical instrument proposed by Schaeffer (1966) and Chion (2009), the present study proposes an intersection between musical instrument and sound installation. The proposal arises from the provocation raised by the work Balance., a sound installation composed using the feedback phenomenon (in which a sound is captured by a microphone, reproduced in a loudspeaker and captured again, causing an infinite cycle to emerge) and the control of its plasticity through a camera that captures the movements of the interactor’s body. A second section is dedicated to reporting the composition and programming process in the Pure Data graphical environment.